Chemometric evaluation of different parameters for removal of tembotrione (agricultural herbicide) from water by adsorption and photocatalytic degradation using sustainable nanotechnology. (3rd February 2022) - Lazarević, Marina; Putnik, Predrag; Šojić Merkulov, Daniela
Abstract: Fractional multivariate design of experiments with seven factors was used to chemometrically evaluate adsorption of tembotrione on the surface of catalyst, efficiency of photocatalytic degradation of tembotrione, and removal efficiency. For adsorption, the experiments revealed two significant main effects (loading of TiO2 and concentration of KBrO3 ) and two interactions (loading of TiO2 × purging of O2 and loading of TiO2 × stirring during and 5 min before irradiation). Model for efficiency of photocatalytic degradation of tembotrione revealed three significant main effects (concentration of KBrO3, purging of O2, and stirring during and 5 min before irradiation), while overall removal efficiency had four significant main effects (concentration of KBrO3, purging of O2, loading of TiO2, and stirring during and 5 min before irradiation) and one two factor interaction (loading of TiO2 × concentration of KBrO3 ). The optimal removal yield of tembotrione was 99.5% with TiO2 loading of 1.25 mg/ml, KBrO3 concentration of 4.33 mM, β‐cyclodextrin with Au in the ratio 2:1, 3 ml/min O2 purging, and stirring before and during irradiation. The effect of tert ‐butanol, NaF, EDTA × 2Na, and p ‐benzoquinone on the tembotrione removal under optimal experimental conditions suggested that the relative contribution of various reactive species changed in following order: O 2 ∙ ‐ ˃ ● OHads ˃ h + ˃ ● OHfree .